Пассивное табакокурение и редуцированное питание беременных – факторы антенатального программирования отклонений сомато-полового развития и структурно-функциональных нарушений в щитовидной железе потомков = Passive smoking and the reduced feeding of pregnant - factors of antenatal programming deviations of somato-sexual development and the structural and functional disorders of the thyroid gland - Sergiyenko, L. Yu.; Yakovtsova, I. I.; Sokolova, S. S.; Postnikov, V. A. (Journal of Education, Health and Sport, 2016)
Sergiyenko L. Yu., Yakovtsova I. I., Sokolova S. S., Postnikov V. A. Пассивное табакокурение и редуцированное питание беременных – факторы антенатального программирования отклонений сомато-полового развития и структурно-функциональных нарушений в щитовидной железе потомков = Passive smoking and the reduced feeding of pregnant - factors of antenatal programming deviations of somato-sexual development and the structural and functional disorders of the thyroid gland. Journal of Education, Health and Sport. 2016;6(2):64-76. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45835 http://ojs.ukw.edu.pl/index.php/johs/article/view/3378 https://pbn.nauka.gov.pl/works/713297 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. Пассивное табакокурение и редуцированное питание беременных – факторы антенатального программирования отклонений сомато-полового развития и структурно-функциональных нарушений в щитовидной железе потомков PASSIVE SMOKING AND THE REDUCED FEEDING OF PREGNANT - FACTORS OF ANTENATAL PROGRAMMING DEVIATIONS OF SOMATO-SEXUAL DEVELOPMENT AND THE STRUCTURAL AND FUNCTIONAL DISORDERS OF THE THYROID GLAND Л. Ю. Сергиенко 1, И. И. Яковцова 2, С. С. Соколова 1,2, А. В. Постников 3 L. Yu. Sergiyenko1, I. I. Yakovtsova2, S. S. Sokolova1,2, V. A. Postnikov3 1ГУ «Институт проблем эндокринной патологии им. .В. Я. Данилевского НАМН Украины», Харьков; 2 Харьковская академия последипломного образования, Харьков 3КУОЗ "Областная детская клиническая больница №1" 1 SI “V.Danilevsky Institute for Endocrine Pathology Problems of the NAMS of Ukraine”, Kharkiv; 2 Kharkiv Medical Postgraduate Academy; 3Regional Children's Hospital №1 Ukraine, Kharkiv Abstract Today proved that the cause of many diseases are unfavorable conditions for the development of the fetus in the womb, caused by exposure to pregnant the toxicants of exogenous nature, which include nicotine, and a violation of its feeding. However, the literature does not answer the question - what is the impact of smoking on pregnant thyropathies development in the offspring. In an experimental model of the combined effects of passive smoking and to reduce energy intake food rats during pregnancy found that their descendants are characterized by a high percentage of deaths in the first months of life, delay physical and sexual development, and at 6 months of age, one-third of the children observed obesity. At the same time, in the offspring of mothers treated with cigarette smoke and having a reduced power during pregnancy, disturbed the dynamics and character formation histostructure and hormonal activity of the thyroid gland. This characteristic becomes microfollicular type of gland structure with hyperthyroidization during puberty, which is replaced by a hypothyroid state, destruction of the parenchyma, the appearance of lymphoid infiltration. Key words: smoking, pregnancy, thyroid gland, offspring. Реферат Сегодня доказано, что причиной многих заболеваний являются неблагоприятные условия развития плода в утробе матери, вызванные воздействием на беременную токсикантов экзогенной природы, к которым относятся никотин, и нарушением ее питания. Но в литературе нет ответа на вопрос - каково влияние курения беременных на развитие тиреопатий у потомков. На экспериментальной модели комбинированного воздействия пассивного курения и снижения калоража питания крыс в течение беременности установлено, что для их потомков характерны высокий процент гибели в первые месяцы жизни, задержка соматического и полового развития, а в 6-месячном возрасте у трети потомков наблюдается ожирение. Одновременно, у потомков матерей обработанных дымом сигарет и имеющих редуцированное питание при беременности, нарушается динамика и характер формирования гистоструктуры и гормональной активности щитовидных желез. При этом характерным становится микрофолликулярный тип строения железы с гипертиреоидизацией в перипубертатном периоде, которая сменяется гипотиреоидным состоянием, деструкцией паренхимы, появлением лимфоидной инфильтрации. Ключевые слова: табакокурение, беременность, щитовидные железы, потомки.